Retração em concreto autoadensável: contribuição de produtos mitigadores - Souza, Andréa Resende (2016)
Self-compacting concrete (CAA) is the concrete of the future for increasing the performance and reducing noise and risk of accidents in the works, besides allowing the execution of slender elements or with a high rate of reinforcement, besides the elimination of the densification process The concrete. However, due to the high content of cement paste and the porous network refinement, there is an increase in the capillary forces and, consequently, increase of the volumetric changes present in the cement matrix, resulting from the retraction process by hydration and drying of the matrix. In this way, this work seeks to evaluate the effectiveness of different retraction mitigation solutions (autogenous and by drying), in CAA mixtures, being used as additions to the study: additive retraction reducer (SRA), compensatory addition of Stype retraction (CSA), polypropylene polymer fiber (FP) and a type of superabsorbent polymer based on potassium polyacrylate (SAP). To analyze the performance of these additions, the retraction tests were performed according to NM 131 (1997) and evaluation of the influence of these additions on the fresh and hardened CAA properties. The CAA mixtures were made with three different cements (CP V ARI, CP II-Z and CP II-E) in combination with three contents of RAS (1%, 1,5% and 2%), with three levels of CSA (3%, 5% and 7%), with three levels of PF (0.05%, 0.10% and 0.15%) and three SPA contents (0.10%, 0.15% and 0.20%) totaling 39 samples. The results of ANOVA showed that both the type of cement and the type of addition significantly influence the properties evaluated in this study, both fresh and hardened. In order to mitigate the autogenous and hydraulic retraction, the influence of cement type and addition was verified, where the use of CP II-Z reduces the retraction between the cements for the control mixtures, and the addition of 7% of CSA results in smaller retractions For all concrete. With the results obtained, it was verified that defining the best type of addition mitigation of retraction to the CAA is a complex process, since it requires, besides the analysis in the laboratory, analysis of its application in the field. It should be noted that the additions are, in different proportions, able to affect in different streets, the retraction and the mechanical properties of the concrete. It should also be noted that both the throughput and the loss of workability are also affected by the choice of cement type, type of addition and content employed. However, in spite of the fact of the occurrence of these changes, it was possible to verify that the concretes produced with cement CP V ARI and polymer fiber, in the contents of 0.05%, or with compensating additive of retraction, in the content of 7%, present Themselves as potentially applicable in various uses.